PEMANFAATAN CANDI MUARA TAKUS SEBAGAI SUMBER BELAJAR DALAM PEMBELAJARAN SEJARAH DI SMA DARMAYUDHA PEKANBARU - Fikri, Asyrul (Sebelas Maret University (UNS), 2019)
This study discusses the utilization of Temple Muara Takus as learning resources in learning history in high school Darmayudha.This research is qualitative research naturalistic. Research data obtained from students and high-school history teacher Darmayudha. Data collection techniques include: observation, interviews, and documentation. Testing the validity of data using triangulation techniques.The analysis of the data used is a model of interactive analysis models Miles and Huberman. Temple Muara Takus utilization as a source of learning gives a positive value for the students. Students become excited and active as well as raise awareness of the importance of students learning history. A visit to the Temple of Muara Takus students as a source of historical study has been hampered at the time of implementation, management and direct the students to focus on learning objectives in the field.